2013
DOI: 10.7860/jcdr/2013/4533.2732
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiological Profiles of Infected Prosthetic Implants with an Emphasis on the Organisms which Form Biofilms

Abstract: Background: In spite of the decreasing incidence of orthopaedic device related infections to 1%, nowadays, device-related infections still remain a diagnostic, therapeutic and cost -related problem. Aims and Objective:To record the common causative organisms and the contributing risk factors for orthopaedic device-related infections in a tertiary care teaching hospital. Methods:In a prospective study, fifty patients who underwent orthopaedic device implantation from Jan 2009 -June 2010 were enrolled; among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 11 publications
6
67
3
1
Order By: Relevance
“…From our study it was found that the most common organism causing orthopedic implant site infection is Staphylococcus aureus which correlates with most of the other similar studies like Anisha Fernandez et al, [2] Khosravi et al [4] and Vishwajith et al [1] The second most common organism isolated was CONS and Eschericia coli. CONS is a normal skin commensal which could have reached the surgical site due to improper disinfection of the skin during surgery or it might be due to improper collection of sample for the diagnosis.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…From our study it was found that the most common organism causing orthopedic implant site infection is Staphylococcus aureus which correlates with most of the other similar studies like Anisha Fernandez et al, [2] Khosravi et al [4] and Vishwajith et al [1] The second most common organism isolated was CONS and Eschericia coli. CONS is a normal skin commensal which could have reached the surgical site due to improper disinfection of the skin during surgery or it might be due to improper collection of sample for the diagnosis.…”
Section: Discussionsupporting
confidence: 76%
“…[11] It is said that with sonication the culture positivity rate can be increased from 84.2% to 94.7%. In our study the culture positivity was found to be 73.01% which is less when compared to other studies where Anisha Fernandez et al [2] reported 84% and Khosravi et al, [4] Vishwajith et al [1] reported the culture positivity of 93.9% and 94.89% respectively. However Gomez et al [12] reported even lesser positivity of 60%.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Klebsiella pneumoniae is a Gram-negative, opportunistic pathogen that is frequently associated with nosocomial infections such as pneumonia, urinary tract infections, and septicemia (1). An important clinical pathogenic mechanism of K. pneumoniae is its ability to form biofilms on inert surfaces such as medical devices, which can lead to rapid microbial colonization on host tissues (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The pathogenicity of K. pneumonia is associated with its ability to form biofilms, which are largely recalcitrant to treatment (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Key to K. pneumonia biofilm development are mannose-resistant Klebsiella-like (Mrk) hemagglutinins or Mrk proteins, which are encoded by the mrkABCDF operon (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%